Optimal Capital Structure Analysis of PT Bluebird TBK - Yuliani, Sri; Kitri, Mandra Lazuardi (Journal of Consumer Studies and Applied Marketing, 2025)
PT Bluebird Tbk, a leading Indonesian road transportation company, plans to acquire 1,000 electric vehicles (EVs) by 2025, which will require an investment of IDR 1.8 trillion. Currently, the company's capital structure consists of 25.24% debt and 74.76% equity, a proportion that differs significantly from the Indonesian road transportation industry average of 51.63% debt and 48.37% equity. This difference suggests that PT Bluebird Tbk may not yet have reached an optimal capital structure. Achieving an optimal mix between debt and equity is important for minimising the company's cost of capital and maximising its overall value. The planned expansion provides an opportunity for PT Bluebird Tbk to evaluate and potentially restructure its capital structure. This study utilised the Cost of Capital approach to identify the optimal capital structure, with the Weighted Average Cost of Capital (WACC) formula to analyse various debt and equity scenarios. The Damodaran Synthetic Rating is utilised to estimate the cost of debt, while the Capital Asset Pricing Model (CAPM) is applied to calculate the cost of equity. The results indicate that the optimal capital structure for PT Bluebird Tbk consists of 32% debt and 68% equity. Therefore, the most favourable financing strategy for the expansion involves raising IDR 742,475 million through debt and IDR 438,711 million through equity to achieve this optimal structure.